The Effectiveness of Cognitive Behavioral Therapy for Reducing Social Anxiety Disorder: A Meta-Analysis - Putra, Timothy Quinn Hartono; Yudiarso, Ananta (Psikostudia : Jurnal Psikologi, 2025)
Social Anxiety Disorder (SAD) is an anxiety disorder characterized by excessive fear of social situations and can impair an individual's interpersonal functioning. The increasing prevalence of SAD in various countries, including Indonesia, has created an urgent need for effective interventions. Cognitive Behavioral Therapy (CBT), in both face-to-face and internet-based formats (Internet-based CBT/ICBT), has become a common approach to treating this disorder. This study aims to evaluate the effectiveness of CBT in reducing SAD symptoms through a meta-analytic method following the PRISMA-P 2020 guidelines. A total of 14 independent studies employing CBT and ICBT were analyzed. The results showed no significant difference in effectiveness between CBT and ICBT, with a small effect size. The modest effectiveness may be due to the use of control groups that received similar behavioral interventions. These findings suggest that both CBT and ICBT can serve as effective and flexible alternatives for addressing SAD, particularly for individuals with limited access to conventional therapy. This study highlights the importance of combining CBT with other therapeutic approaches and emphasizes the need to consider cultural context in the implementation of therapy.Social Anxiety Disorder (SAD) merupakan gangguan kecemasan yang ditandai dengan ketakutan berlebihan terhadap situasi sosial dan dapat menghambat fungsi interpersonal individu. Peningkatan prevalensi SAD di berbagai negara, termasuk Indonesia, menimbulkan kebutuhan mendesak akan intervensi yang efektif. Cognitive Behavior Therapy (CBT), baik dalam pendekatan tatap muka maupun berbasis internet (Internet-based CBT/ICBT), telah menjadi pendekatan umum untuk mengatasi gangguan ini. Penelitian ini bertujuan untuk mengevaluasi efektivitas CBT dalam menurunkan gejala SAD melalui metode meta-analisis yang mengikuti prosedur PRISMA-P 2020. Sebanyak 14 studi independen yang menggunakan CBT dan ICBT dianalisis. Hasil menunjukkan bahwa tidak terdapat perbedaan signifikan dalam efektivitas antara CBT dan ICBT, dengan nilai effect size kecil (small effect size). Rendahnya efektivitas kemungkinan disebabkan oleh penggunaan kelompok kontrol dengan intervensi sejenis, seperti terapi perilaku lain. Temuan ini mengindikasikan bahwa baik CBT maupun ICBT dapat menjadi alternatif intervensi yang efektif dan fleksibel dalam menangani SAD, terutama bagi individu dengan keterbatasan akses terhadap terapi konvensional. Penelitian ini menyarankan perlunya kombinasi CBT dengan pendekatan lainnya serta pentingnya mempertimbangkan konteks budaya dalam implementasi terapi.